The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1186/1745-6150-2-31
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the protein coding potential of exonized transposable element sequences

Abstract: Background: Transposable element (TE) sequences, once thought to be merely selfish or parasitic members of the genomic community, have been shown to contribute a wide variety of functional sequences to their host genomes. Analysis of complete genome sequences have turned up numerous cases where TE sequences have been incorporated as exons into mRNAs, and it is widely assumed that such 'exonized' TEs encode protein sequences. However, the extent to which TE-derived sequences actually encode proteins is unknown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 58 publications
4
27
0
Order By: Relevance
“…The remaining five exons were in coding regions, including two that introduced premature termination codons. This distribution is consistent with the hypothesis that most functional Alu exonization events do not contribute to the proteome but may play a role in regulating gene expression [46],[47]. Similar to the finding by a recent study of species-specific exons [48], we observed an excess of Alu-derived internal exons in 5′-UTR as compared to 3′-UTR.…”
Section: Resultssupporting
confidence: 92%
“…The remaining five exons were in coding regions, including two that introduced premature termination codons. This distribution is consistent with the hypothesis that most functional Alu exonization events do not contribute to the proteome but may play a role in regulating gene expression [46],[47]. Similar to the finding by a recent study of species-specific exons [48], we observed an excess of Alu-derived internal exons in 5′-UTR as compared to 3′-UTR.…”
Section: Resultssupporting
confidence: 92%
“…TE-related genes were detected using hmmsearch50 v3.1b2 (trusted cutoff) using 137 identified TE-related domains51.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the choice of sequence similarity search methods to detect TE–derived sequences strongly influences the estimate of TE-cassettes that can be identified in protein coding regions [46] . Hidden Markov model based searches followed by BLAST methods (tBLASTx → tBLASTn → BLASTx → BLASTp → BLASTn) and RepeatMasker are more sensitive in identifying exonized TEs.…”
Section: Methodsmentioning
confidence: 99%